Distribution of VDR Gene Polymorphisms Bsm-I rs1544410 and Apa-I rs7975232 among HIV/AIDS Patients from West Java - Hendro Hendro; Edhyana Sahiratmadja; Agnes Rengga Indrati; Ani Melani Maskoen (Faculty of Medicine, Universitas Padjadjaran, 2020)
Vitamin D receptor, encoded by VDR gene, mediates vitamin D functions by not only regulating calcium metabolism and homeostasis but also in regulating immune response. Polymorphisms in VDR gene may increase the progression of human immunodeficiency virus (HIV) infection into acquired immunodeficiency syndrome (AIDS). This study aimed to explore the distribution of VDR polymorphisms among HIV sero-positive patients in West Java. A cross-sectional study was performed, recruiting 96 patients infected with HIV and VDR polymorphisms were analyzed. The genotype distributions of Bsm-I among HIV-infected patients were 2.2%, 18.5%, and 79.3% for BB, Bb, and bb, respectively whereas the distributions of Apa-I were 54.4%, 38.9%, and 6.7% for AA, Aa and aa, respectively. The frequency of VDR polymorphisms in Bsm-I among HIV-infected patients in West Java were considered high for b allele (88.6%), and in contrast for A allele in Apa-I that was 73.91%. Further studies involving healthy controls are needed to explore the VDR polymorphisms distribution in general population. Moreover, a cohort study, albeit challenging, is needed to further assess the association between VDR polymorphisms and the progression of HIV infection.Distribusi Polimorfisme gen VDR Bsm-I rs1544410 dan Apa-I rs7975232 pada Pasien HIV/AIDS di Jawa BaratReseptor vitamin D yang dikode oleh gen VDR mempunyai peranan penting terhadap fungsi vitamin D, tidak hanya dalam regulasi metabolisme dan keseimbangan kalsium namun juga berperan dalam meregulasi respon imun. Polimorfisme pada gen VDR ditengarai dapat meningkatkan progresivitas infeksi human immunodeficiency virus (HIV) menjadi acquired immunodeficiency syndrome (AIDS). Penelitian ini bertujuan mengetahui distribusi polimorfisme gen VDR pada pasien HIV di Jawa Barat. Penelitian ini melibatkan 96 pasien HIV dan dilakukan analisis polimorfisme gen VDR. Distribusi genotip Bsm-I pada pasien HIV di Jawa Barat adalah 2,2%, 18,5%, dan 79,3% untuk BB, Bb, dan bb, secara beurutan; sedangkan pada Apa-I adalah 54,4%, 38,9%, dan 6,7% untuk AA, Aa, dan aa. Frekuensi polimorfisme pada Bsm-I pada pasien HIV di Jawa Barat tergolong tinggi pada alel b (88,6%) dan berbanding terbalik pada dan Apa-I dengan alel A yaitu 73,91%. Penelitian lebih lanjut yang melibatkan individu kontrol diperlukan untuk mengetahui distribusi polimorfisme gen VDR pada populasi umum. Selain itu, studi kohort pada pasien HIV/AIDS diperlukan untuk menilai hubungan antara polimorfisme gen VDR terhadap progresivitas infeksi HIV.